Measurement of the B-c(-) meson lifetime in the decay B-c(-) -> J/psi pi(-) - Aaltonen, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2013)
The lifetime of the Bc- meson is measured using 272 exclusive Bc-→J/ψ(→μ+μ-)π- decays reconstructed in data from proton-antiproton collisions corresponding to an integrated luminosity of 6.7 fb-1 recorded by the CDF II detector at the Fermilab Tevatron. The lifetime of the Bc- meson is measured to be τ(Bc-)=0.452±0.048(stat)±0.027(syst) ps. This is the first measurement of the Bc- meson lifetime in a fully reconstructed hadronic channel, and it agrees with previous results and has comparable precision. © 2013 American Physical Society.